Paraclinical findings in Iranian veterans exposed to sulfur mustard gas: A literature review - Seyed Mansour Razavi (Chinese Journal of Traumatology, 2017)
Objective: Sulfur mustard (SM) causes various systemic disturbances in human beings. This study aimed to assess paraclinical changes caused by exposure to SM gas in Iranian veterans during the war between Iraq and Iran. Methods: A literature review was carried out in international and national medical databases including ISI, Medline, Scopus, Iranmedex and Irandoc. Both Farsi and English literature were searched. Results: Search of the literature yielded 422 medical articles related to SM poisoning. Among them, 30 relevant articles were thoroughly reviewed. The most important reported complications were leukopenia, neutropenia, lymphopenia, eosinophilia, thrombocytopenia, increased bleeding time, positive C-reactive protein (CRP), rheumatoid factor (RF), antinuclear antibody (ANA), decreased T helper cells, natural killer cells, IL6, and IL8 levels, elevation of serum immunoglobulins, decreased levels of T3, T4 and cortisol, increased level of adrenocorticotropic hormone (ACTH), proteinuria, hematuria, and elevated liver enzymes. Also, there were some changes in chest assessments. Conclusions: SM causes profound systemic complications in victims, even years after exposure. The paraclinical changes can be observed in hematology, immune system, biochemistry, hormonal profile and some imaging studies.